The Effect of Green Intellectual Capital, Good Corporate Governance, and Growth Options on Sustainability Performance - Husnul Khotimah; Endang Ruhiyat; Dani Rahman Hakim (Journal of Economics, Business, and Accountancy Ventura, 2024)
Global climate change, deforestation, plastic pollution, and other environmental issues have made sustainability performance an increasingly researched topic. This study investigates the impact of green intellectual capital, good corporate governance, and growth options on the sustainability performance of primary consumer goods sector companies in Indonesia. Additionally, it examines the moderating role of public ownership. We measure sustainability performance using a composite index based on the sustainability balanced scorecard and the G4 Global Reporting Initiative's sustainability reporting disclosure framework. To our knowledge, this study is the first to employ this specific measurement method. Using a random effects estimator on 144 observations, we estimated our models. The findings indicate that good corporate governance, growth options, and public ownership positively influence sustainability performance, while green intellectual capital does not. Furthermore, the study reveals that public ownership strengthens the effects of green intellectual capital and growth options on sustainability performance. This suggests that in companies with low public ownership, green intellectual capital alone may not sufficiently enhance sustainability performance.